Identification of metabolic and biomass QTL in Arabidopsis thaliana in a parallel analysis of RIL and IL populations - Lisec, Jan; Meyer, Rhonda C.; Steinfath, Matthias; Redestig, Henning; Becher, Martina; Witucka‐Wall, Hanna; Fiehn, Oliver; Törjék, Ottó; Selbig, Joachim; Altmann, Thomas; Willmitzer, Lothar (The Plant journal : for cell and molecular biology, 2008)
Summary Plant growth and development are tightly linked to primary metabolism and are subject to natural variation. In order to obtain an insight into the genetic factors controlling biomass and primary metabolism and to determine their relationships, two Arabidopsis thaliana populations [429 recombinant inbred lines (RIL) and 97 introgression lines (IL), derived from accessions Col‐0 and C24] were analyzed with respect to biomass and metabolic composition using a mass spectrometry‐based metabolic profiling approach. Six and 157 quantitative trait loci (QTL) were identified for biomass and metabolic content, respectively. Two biomass QTL coincide with significantly more metabolic QTL (mQTL) than statistically expected, supporting the notion that the metabolic profile and biomass accumulation of a plant are linked. On the same basis, three out the six biomass QTL can be simulated purely on the basis of metabolic composition. QTL based on analysis of the introgression lines were in substantial agreement with the RIL‐based results: five of six biomass QTL and 55% of the mQTL found in the RIL population were also found in the IL population at a significance level of P ≤ 0.05, with >80% agreement on the allele effects. Some of the differences could be attributed to epistatic interactions. Depending on the search conditions, metabolic pathway‐derived candidate genes were found for 24–67% of all tested mQTL in the database AraCyc 3.5. This dataset thus provides a comprehensive basis for the detection of functionally relevant variation in known genes with metabolic function and for identification of genes with hitherto unknown roles in the control of metabolism.